PENGARUH RETURN ON ASSET, EARNING PER SHARE DAN DIVIDEN PAYOUT RATIO TERHADAP HARGA SAHAM (Studi Pada Perusahaan Yang Terdaftar di LQ 45 Tahun 2013 – 2015) - Dwi Meranti, 15.05.51.0351; Irsad, Moch. (Students' Journal of Economic and Management, 2019)
This study examines the Effect of Return On Assets, Earning Per Share and Dividend Payout Ratio on Stock Prices in Companies Listed in LQ 45 in 2013 - 2015) The population in this study was a company registered in LQ 45. The research samples with predetermined criteria were 111 companies. With Purposive sampling method or sampling technique with certain considerations or criteria during 2013-2015, so the number of samples (n) = 111. While the method used is Multiple Regression Analysis. The test results obtained that the variable Return on Assets (ROA) has a significant positive effect on stock prices, Earning Per Share (EPS) has no significant negative effect on stock prices and Dividend Payout Ratio (DPR) has a positive and not significant effect on stock prices.